Business cycles in a small open economy with a banking sector - Oviedo, Pedro Marcelo (2001)
This paper studies the interest-rate-driven business cycles of a small open economy (SOE). For than end a costly operated banking system is added to the standard real-business-cycles model. Banks are the only domestic agents considered worthy of credit in international capital markets. They borrow from the rest of the world and lend domestically in a competitive credit market. Existent quantitative models of business cycles in SOE's indicate that interest-rate shocks are unable to cast the kind of output variability produced by productivity or terms-of-trade shocks. Contrary to this finding, it seems that the macroeconomic performances of several SOE's are tightly related to international interest rates and capital flows. Neumeyer and Perri (1999) points out that the introduction of working capital needs may close the gap between the standard model's predictions and the observed consequences of interest-rate shocks. This paper shows that a more careful analysis of the microfoundations of working capital may give rise to an intermediate position where working capital matters in explaining output fluctuations, but not as much as Neumayer and Perri suggest. For that end, the model is calibrated to the Argentinean economy.